The Post-Boom in Spanish American Fiction - Donald L. Shaw (Studies in 20th & 21st Century Literature, 1995)
The article discusses the dating of the beginning of the Post-Boom, the factors involved in discussing it, and lists possible representative writers belonging to it. The views of Skármeta, Allende and others are reported and a list of possible Post-Boom characteristics is suggested. It is argued that there are difficulties in the way of relating the Post-Boom easily to Postmodernism, but that the notion of Post-colonialism may prove helpful in future criticism.
Keywords: Post-boom; Skármeta; Allende; postmodernism; post-colonialism